Teste de identificação de sentenças com figuras: elaboração e validação - Vellozo, Fernanda Freitas (2016)
Objectives: To elaborate, validate and generate reference values of a test for adults (Teste de Identificação de Sentenças com Figuras (TIS-F)) which is an alternative to the auditory ability of figure-background evaluation for verbal sounds in adults, using figures, based on the Pediatric Speech Audiometry Test (PSAT) and for evaluation of unskillful individuals to accomplish other tests with difficulty and greater demands. In addition, to realize gender analysis to the TIS-F, to compare the performance of the subjects in both tests (PSAT and TIS-F) and compare the PSAT results to the existing normality criteria for it. Methods: To prepare the TIS-F, in the creation of the figures phase, the Adobe Illustrator software was used and the images vectorization technique was applied, being chosen images of reference derived from image sites, handled by a professional in the field and conducted the necessary changes in them, creating its own design. In the recording phase, a female announcer, using the program - REAPER - FM Digital Audio Workstation and a sound table model Audioarts D75 Digital Audio Console, held both the competitive message and the sentences in a recording studio in the Universidade Federal de Santa Maria, in an acoustic treated room. The microphone used was a model RE27 Electro Voice. Fifty individuals, being 25 female and 25 male, aging between 18 and 33 years old, presenting normal hearing and being right-handed, composed the sample. All the subjects were submitted to an audiological evaluation (Pure-Tone Threshold Audiometry, Logoaudiometry, and Acoustic Immittance Measures) and the auditory processing tests (Dichotic Sentences Identification (DSI) and PSAT) to characterize the sample and the included subjects also performed the TIS-F. Results: The TIS-F was prepared and consisted of a cart of 32 x 45 cm, with 10 figures, each one measuring 12 x 12 cm; one compact disc containing the test calibration tone and seven test tracks, each one containing ten sentences and a competitive message and; a specific protocol of it. It was observed that there was no influence of gender on the performance of subjects for TIS-F and the values obtained as the reference were 100% for all relations signal / noise (S/N). The subjects presented similar performance in both tests (PSAT and TIS-F), except for ipsilateral competitive message (ICM) in the relation S/N -15 dB. The founded values to PSAT in adults are superior to existing normality criteria for the infant population. Conclusion: It was possible to elaborate, validate and generate TIS-F test reference values for an adult population. There was not performance difference between PSAT and TIS-F, except in the ICM -15dB phase. There is statistically significant difference between the established criteria for the PSAT and the results obtained in this study with better results for individuals surveyed in the present study.